WorldWater: putting the community in charge - Herrman, John (Technical Centre for Agricultural and Rural Cooperation, 2003)
Using a down-to-earth mixture of technology and community participation, the WorldWater programme in the Philippines is developing locally owned and managed water systems that use renewable solar energy and smart card technol